Selection of a set of earthmoving equipment in the aspect minimizing the emission of CO2 - Rogalska, Magdalena (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The aim of the calculation is to allow the selection of a set of earthmoving machinery in terms of minimizing the emission of CO2. The capacity of excavators and CO2 emission of set of machines was predicted. The forecasting methods: multiple regression and neural networks were used. The analysis of autocorrelation and partial autocorrelation residuals and sensitivity analysis were performed. The MAPE errors of forecasts were calculated. The calculation example in terms of selection of machines emission of carbon dioxide on the basis of forecasting models was performed.